2005
DOI: 10.1091/mbc.e05-04-0330
|View full text |Cite
|
Sign up to set email alerts
|

Myosin 2 Is a Key Rho Kinase Target Necessary for the Local Concentration of E-Cadherin at Cell–Cell Contacts

Abstract: Classical cadherins accumulate at cell-cell contacts as a characteristic response to productive adhesive ligation. Such local accumulation of cadherins is a developmentally regulated process that supports cell adhesiveness and cell-cell cohesion. Yet the molecular effectors responsible for cadherin accumulation remain incompletely understood. We now report that Myosin 2 is critical for cells to concentrate E-cadherin at cell-cell contacts. Myosin 2 is found at cadherin-based cell-cell contacts and its recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
309
2
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 339 publications
(361 citation statements)
references
References 46 publications
41
309
2
9
Order By: Relevance
“…As a result, we found that Y27632 dissociated myosin-2 from the ZA, consistent with a previous report on MCF7 cells (Shewan et al, 2005). Phosphorylation of myosin-2 is reportedly a downstream event in the ROCK pathway.…”
Section: Dissociation Of Myosin-2 From Za By Latrunculin a Blebbistasupporting
confidence: 93%
“…As a result, we found that Y27632 dissociated myosin-2 from the ZA, consistent with a previous report on MCF7 cells (Shewan et al, 2005). Phosphorylation of myosin-2 is reportedly a downstream event in the ROCK pathway.…”
Section: Dissociation Of Myosin-2 From Za By Latrunculin a Blebbistasupporting
confidence: 93%
“…20 We then examined the localization of non-muscle myosin II in MCF-7 cells depleted of Coronin 1B, as E-cadherin and F-actin have been shown to influence the recruitment of non-muscle myosin II to junctions. 4,6,19 As previously described, 4,6,19 NMIIA and NMIIB concentrated prominently at the zonulae adherente of control MCF-7 monolayers (Fig. 1D, E).…”
Section: Resultssupporting
confidence: 75%
“…Since NMIIA was more stable at the ZA than in other regions of cell-cell junctions, this defined where the junctional RhoA zone was established. 7 In addition to activation by RhoA-ROCK signaling 2,19 , the junctional localization of NMIIA can also be influenced by the F-actin networks with which it associates. 20,21 Actin regulators comprise actin polymerization factors as well as regulators of F-actin architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Nonmuscle myosin (NM) II, one of the major cytoskeletal motor proteins, plays an important role in cell migration (Svitkina et al, 1997;Ma et al, 2004;Even-Ram et al, 2007;Vicente-Manzanares et al, 2007), cell-cell adhesion Shewan et al, 2005;Giannone et al, 2007), and cell division (De Lozanne and Spudich, 1987;Takeda et al, 2003;Bao et al, 2005). The molecular structure of NM II is a hexamer consisting of a pair of myosin heavy chains (200 kDa) and two pairs of light chains (20 and 17 kDa).…”
Section: Introductionmentioning
confidence: 99%
“…The defect may be accompanied by an obstructed aqueduct of Sylvius, the narrow channel connecting the third and fourth brain ventricles (noncommunicating hydrocephalus), or by a normal aqueduct (communicating hydrocephalus). The pathogenesis of most cases of communicating hydrocephalus is largely unknown (for reviews, see Perez-Figares et al, 2001;Crews et al, 2004).Nonmuscle myosin (NM) II, one of the major cytoskeletal motor proteins, plays an important role in cell migration (Svitkina et al, 1997;Ma et al, 2004;Even-Ram et al, 2007;Vicente-Manzanares et al, 2007), cell-cell adhesion Shewan et al, 2005;Giannone et al, 2007), and cell division (De Lozanne and Spudich, 1987;Takeda et al, 2003;Bao et al, 2005). The molecular structure of NM II is a hexamer consisting of a pair of myosin heavy chains (200 kDa) and two pairs of light chains (20 and 17 kDa).…”
mentioning
confidence: 99%